2012
DOI: 10.1177/1468087412456688
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental spray and combustion measurements of soy methyl-ester biodiesel

Abstract: Nerva, J.; Genzale, CL.; Kook, S.; García Oliver, JM.; Pickett, LM. (2013) soy methyl-ester biodiesel is injected into a constant-volume combustion facility. A range of optical diagnostics is performed, comparing biodiesel to a conventional #2 diesel at the same injection and ambient conditions. Schlieren imaging shows virtually the same vapor-phase penetration for the two fuels, while simultaneous Mie-scatter imaging shows that the maximum liquid-phase penetration of biodiesel is higher than diesel due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 67 publications
(159 reference statements)
2
72
0
Order By: Relevance
“…10. Measured [58] and predicted liquid spray penetration and vapor penetration vs. time for biodiesel fuel at an ambient temperature of 900 K. Fig. 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10. Measured [58] and predicted liquid spray penetration and vapor penetration vs. time for biodiesel fuel at an ambient temperature of 900 K. Fig. 11.…”
Section: Discussionmentioning
confidence: 99%
“…25% MD, 25% MD9D and 50% nheptane in mole fraction, is used in the simulations. The experimental dataset was obtained by the Sandia National Laboratories [58], where a constant-volume, quiescent, pre-burn-type combustion vessel was used to generate high-temperature and high-pressure gases. A premixed combustible mixture was spark-ignited and the combustion products cool over a long time.…”
Section: -D Simulations At CI Engine Conditionsmentioning
confidence: 99%
“…Moreover, the model indicated the presence of an "entrainment wave" that travels along the jet from upstream, promoting fuel air mixing after EOI. This model has been also used to explain results obtained by means of combustion vessels [14] and optical single-cylinder research engine [29] [30].…”
Section: Introductionmentioning
confidence: 99%
“…are observed to have a significant effect on lift-off length and ignition delay [2]. Vapour and liquid penetration of soy biodiesel and diesel along with spray combustion characteristics are studied by Nerva et al [63] which showed that, in spite of having a higher liquid penetration for biodiesel, both biodiesel and diesel have similar vapour penetration. Higher peak heat release rate and shorter combustion duration were observed for biodiesels as compared to diesel indicating faster combustion [64,65].…”
Section: Evaporating and Combusting Spraysmentioning
confidence: 99%
“…Significant reduction in soot production is observed in biodiesel spray combustion. It is believed that the presence of oxygen in biodiesel is mainly responsible for the soot reduction [63,66]. In the quasi-steady diffusion combustion phase, physical processes such as evaporation and mixing are observed to have a major effect on ignition and combustion processes.…”
Section: Evaporating and Combusting Spraysmentioning
confidence: 99%